2005
DOI: 10.1080/08927014.2005.9522603
|View full text |Cite
|
Sign up to set email alerts
|

The frontal shield of the moorhen: sex differences and relationship with body condition

Abstract: Moorhens Gallinula chloropus have a conspicuous frontal shield, which is used in competitor assessment, and whose size and colour is testosteronedependent in both sexes. During 2 months in winter we examined sex-related differences in size and colour of the red or red-orange shield and the yellow-tipped bill of free-living adult moorhens, as well as their relationship with indices of body condition (body size, tarsi fluctuating asymmetry, fat index, serum lutein carotenoid concentration, and a number of blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 64 publications
1
8
1
Order By: Relevance
“…Contrary to expectations, the size of the frontal shield was not included in the developed discriminant functions, although this trait is known to show apparent sexual dimorphism in different species of the Rallidae family (Alvarez et al 2005;Dey et al 2012). Using within-pair differences in the frontal shield size to infer the sex of breeding Eurasian Coots has been reported in the field (Salathé and Boy 1987;Zhang and Ma 2012).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Contrary to expectations, the size of the frontal shield was not included in the developed discriminant functions, although this trait is known to show apparent sexual dimorphism in different species of the Rallidae family (Alvarez et al 2005;Dey et al 2012). Using within-pair differences in the frontal shield size to infer the sex of breeding Eurasian Coots has been reported in the field (Salathé and Boy 1987;Zhang and Ma 2012).…”
Section: Discussioncontrasting
confidence: 67%
“…The frontal shield in Rallidae is typically used by conspecifics as a cue of individual quality during intra-and inter-sexual interactions, primarily during fighting for mates, territory defense and courtship. There is evidence that the shield size in Rallidae is a reliable signalling ornament, as it correlates with body condition or health (Alvarez et al 2005), age (Visser 1988) and dominance status (Crowley and Magrath 2004;Dey et al 2014). The frontal shield size was also confirmed to be testosterone-dependent in several species of ralids (Gullion 1951;Eens et al 2000), and, therefore, it has ability to change over a short period of time (Dey et al 2014).…”
Section: Discussionmentioning
confidence: 91%
“…This finding is consistent with the results of studies of other species, which have demonstrated links between frontal shield characteristics and aspects of individual quality (Fenoglio et al 2002, Alvarez et al 2005. The size of the testes is correlated with circulating testosterone levels in many birds (Garamszegi et al 2005), and therefore our results are consistent with a relationship between androgens and frontal shield size in Pūkeko.…”
Section: Discussionsupporting
confidence: 82%
“…T treatment in this species, however, did not increase nuptial head coloration FA indicating that asymmetry was not affected by the presumable physiological stress induced by T implementation. Similarly, no significant associations were found between tarsi FA and T-dependent frontal shield size and color in moorhens [81].…”
Section: Nonhuman Animal Studiesmentioning
confidence: 71%